MicroRNA-409-3p promotes osteoblastic differentiation via activation of Wnt/β-catenin signaling pathway by targeting SCAI. Issue 1 (29th January 2021) - Chen, Nan; Yang, Hao; Song, Lijun; Li, Hua; Liu, Yi; Wu, Di
Abstract: Osteogenic differentiation is an important process of new bone formation, microRNA-409-3p (miR-409-3p) has been reported to be up-regulated in the osteogenic differentiation of human bone marrow mesenchymal stem cells (MSCs). The present study aimed to investigate the regulatory effect of miR-409-3p on osteogenic differentiation of MSCs and its molecular mechanism. The expression of miR-409-3p in osteoblast (human skull osteoblast, HCO) and bone marrow-derived MSCs (MSC-A, MSC-B, MSC-U) were detected by reverse transcription-quantitative polymerase chain reaction (RT-qPCR). The binding of miR-409-3p to suppressor of cancer cell invasion ( SCAI ) in MSC-B was investigated by performing a dual-luciferase reporter gene assay. MSC-B was selected to transfect with miR-409-3p analog/complementary sequence (cs), miR-409-3p analog + SCAI and miR-409-3p cs + small interfering (si)-SCAI, as well as control, respectively. The alkaline phosphatase (ALP) activity, Alizarin Red staining, and the expression of osteogenic markers (ALP, osteocalcin (OCN), osteopontin (OPN), runt-related transcription factor 2 (RUNX2)) in MSC-B during osteoblastic differentiation were tested by RT-qPCR and Western blotting, respectively. Additionally, the Wnt/β-catenin pathway was inhibited by dickkopf-related protein 1 (DKK-1) to get the roles of miR-409-3p during the osteoblastic differentiation of MSC-B when transfected with miR-409-3p analog. The expression of miR-409-3p in HCO was higher than that in these three MSCs and showed an increasing time-dependent trend on the 0 and 21st day of osteoblastic differentiation. MiR-409-3p directly regulated SCAI by targeting SCAI 3′UTR. Further, miR-409-3p suppressed SCAI expression, but SCAI up-regulation suppressed the osteoblastic differentiation, as well as reduced the relative mRNA/protein expression of Wnt/β-catenin signaling pathway-related genes (Axis inhibition protein 1 (AXIN1), β-catenin, Lymphoid Enhancer Binding Factor 1, Cellular-myelocytomatosis (c-myc) and cyclin D1). Importantly, disruption of Wnt signaling also blocked miR-409-3p induced osteoblastic differentiation of MSCs. Therefore, miR-409-3p promotes osteoblastic differentiation through the activation of the Wnt/β-catenin pathway by down-regulating SCAI expression.